Know your mind : the complete family reference guide to emotional health - Freeman, Daniel, 1971-; Freeman, Jason (Jason Ryan) (New York, NY : Sterling, 2010)
Provides "self-diagnosis tools and tests, when to seek professional help, simple plans for staying well, comprehensive list of resources, special section for children"--Dust jacket.
Reprint of the 1st ed. originally published: Emmaus, Pa. : Rodale, 2009.
Includes bibliographical references and index.
Keywords: Psychology, Pathological -- Popular works; Mental health -- Popular works